2012
DOI: 10.2340/00015555-1178
|View full text |Cite
|
Sign up to set email alerts
|

Genotype–Phenotype Correlation in Chinese Patients with Dystrophic Epidermolysis Bullosa Pruriginosa

Abstract: Dystrophic epidermolysis bullosa pruriginosa (DEB-Pr) is a rare variant of dystrophic epidermolysis bullosa (DEB) due to dominant or recessive mutations in the COL7A1 gene. More than 40 mutations in COL7A1 have been described in DEB-Pr. The aim of this study was to understand the genotype-phenotype correlation in Chinese patients with DEB-Pr. Three Chinese families with typical clinical features of DEB-Pr were studied. The results were analysed in association with the eight Chinese DEB-Pr patients reported in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 20 publications
1
17
1
Order By: Relevance
“…To date, including this study, there have been 52 mutations in the COL7A1 gene reported in association with EBP, of which 35 mutations are glycine substitutions in the first amino acid of the Gly–X–Y repeats located in the triple‐helix region, indicating that glycine substitution is the most common mutations underlying EBP. The recurrent mutation p.G2287R in patient 2 (FEBP) was initially reported in a patient with recessive dystrophic EB, whereas that patient's mother, the heterozygous carrier of this mutation, presented only with nail deformity restricted to the great toes .…”
Section: Col7a1 Mutations In Patients With Epidermolysis Bullosa Prurmentioning
confidence: 77%
See 1 more Smart Citation
“…To date, including this study, there have been 52 mutations in the COL7A1 gene reported in association with EBP, of which 35 mutations are glycine substitutions in the first amino acid of the Gly–X–Y repeats located in the triple‐helix region, indicating that glycine substitution is the most common mutations underlying EBP. The recurrent mutation p.G2287R in patient 2 (FEBP) was initially reported in a patient with recessive dystrophic EB, whereas that patient's mother, the heterozygous carrier of this mutation, presented only with nail deformity restricted to the great toes .…”
Section: Col7a1 Mutations In Patients With Epidermolysis Bullosa Prurmentioning
confidence: 77%
“…In our second case, all the affected family members carrying the p.G2287R mutation developed moderate to serious prurigo‐like lesions and pruritus during the third decade of life. Another recurrent mutation, p.G2701W, which was detected in patient 6 (SEBP) was recently reported in a female Chinese patient with EBP, whose clinically unaffected mother carried the same mutation . In that study, the author was unable to exclude the possibility of recessive inheritance of the mutation p.G2701W.…”
Section: Col7a1 Mutations In Patients With Epidermolysis Bullosa Prurmentioning
confidence: 93%
“…[3][4][5][6][7][8][9] Comparing dystrophic epidermolysis bullosa and epidermolysis bullosa pruriginosa, there is generally no clear genotype-phenotype correlation although skipping of exon 87 in the COL7A1 gene can be associated with the dominantly-inherited form of epidermolysis bullosa pruriginosa. [7][8][9] The novel dominant-negative heterozygous acceptor splice site mutation in the COL7A1 gene (IVS67-1G>T) was found in both our patient and his youngest son, who was 34 years old at the time of testing. The latter can reasonably be assumed to be at risk of developing epidermolysis bullosa pruriginosa in the future and should receive treatment as soon as symptoms arise.…”
Section: Discussionmentioning
confidence: 95%
“…DEB-Pr, a rare subtype of DEB, also shows genetic heterogeneity, as autosomal dominant and recessive inheritance patterns have been previously reported (Jiang et al, 2012). COL7A1 gene mutations have been demonstrated to cause the entity (Christiano et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, COL7A1 gene mutations can influence the biosynthesis of collagen VII, resulting in different phenotypes of DEB-Pr (Drera et al, 2006;Dang and Murrell, 2008). Furthermore, although additional immune-mediated factors may be involved in the pathogenesis of DEB-Pr (Jiang et al, 2012), it is unclear whether other genetic, epigenetic, metabolic, or environmental factors contribute to the DEB-Pr phenotype (Almaani et al, 2009). …”
Section: Discussionmentioning
confidence: 99%